Global burden and cross-country inequalities of gallbladder and biliary tract cancer in adults aged 45 years and older from 1990 to 2021: population-based study - Lei, Simeng; Fu, Yangkai; Zhang, Bo; Yang, Hanwen; Hu, Yang; Ji, Zhili (Frontiers in Oncology, 2025)
ObjectiveGallbladder and biliary tract cancers (GBTC) remain a global health burden, particularly in adults aged 45 years and older. Understanding trends, regional disparities, and risk factors is crucial for guiding public health strategies. This study aimed to evaluate the global, regional, and national patterns of GBTC burden from 1990 to 2021, with a focus on socio-demographic variations and cross-country inequalities.MethodsData were obtained from the Global Burden of Disease (GBD) 2021 study, covering 204 countries and territories. Age-standardized incidence rates (ASIR), age-standardized prevalence rates (ASPR), age-standardized mortality rates (ASMR), and age-standardized disability-adjusted life years rates (ASDR) were calculated. Temporal trends were assessed using estimated annual percentage changes (EAPC). Frontier and decomposition analyses were conducted to identify drivers of changes, and the role of high body mass index (BMI) and population aging was examined.ResultsIn 2021, the global ASIR of GBTC was 9.04 per 100,000, showing an annual decline of 0.453%. However, ASPR increased slightly by 0.240% per year. The ASDR and ASMR declined annually by 1.080% and 0.903%, respectively. High-SDI regions exhibited increasing incidence due to epidemiological transitions, while low-SDI regions were more affected by aging populations. Frontier analysis revealed widening disparities between high- and low-SDI countries. High BMI was identified as a major risk factor, contributing significantly to DALYs and mortality, particularly in high-income regions such as North America. Individuals aged 50–54 had the highest burden attributable to high BMI, accounting for 13.08% of DALYs and 13.06% of deaths. Cross-country analysis indicated persistent inequalities, with higher incidence concentrated in high-SDI countries. Although relative inequalities in prevalence and mortality narrowed modestly between 1990 and 2021, substantial disparities across SDI levels remain.ConclusionAlthough the global burden of GBTC has declined in mortality and DALYs, incidence trends remain concerning, especially in high-SDI countries. Regional disparities persist and have widened over time, with high BMI and population aging as key drivers. While certain indicators suggest modest narrowing of inequalities, large gaps between SDI regions remain. Public health policies should focus on mitigating these disparities, particularly by addressing high BMI and strengthening interventions in low-SDI regions to further reduce the burden of GBTC.